Biochemical and Dielectric Characteristics of Follicular Fluid from Human Ovary after Freezing-Thawing - Gerodes, A. G.; Gorobchenko, O. A.; Nardid, O. A.; Nikolov, O. T.; Rozanova, E. D. (Problems of Cryobiology and Cryomedicine, 2010)
The effects of a follicle size, total protein, sugar and hormone (estradiol, testosterone, progesterone) contents as well as freezing up to â€“196Â°C and storage in liquid nitrogen on water state in follicular fluid (FF) of the human ovary were studied. An enhancement in the frequency of dielectric relaxation of molecules in FF with a follicle size increasing was discovered. A close dependence of FF component hydration on a follicle diameter was revealed. It was shown that a rapid freezing and storage caused a decrease in the frequency of dielectric relaxation of water molecules in FF, which could be a result of a gain in the quantity of bound water in the system.